The Relationship of Placental Weight with Birth Weight - Kabir, N; Kawser, CA; Rahman, F; Kabir, ML; Rahman, A (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 177-180 The abstract of this article is available on the PubMed website